1976
DOI: 10.1007/bf00237323
|View full text |Cite
|
Sign up to set email alerts
|

The avian pineal organ. Distribution of exogenous indoleamines: A qualitative study of the rudimentary photoreceptor cells by electron microscopic radioautography

Abstract: The uptake of 5-hydroxytryptophan (3H-5-HTP) and serotonin (3H-5-HT) and their distribution have been demonstrated, at the ultrastructural level, in the secretory rudimentary photoreceptor cells (SRP cells), in the pineal organ of the parakeet and the duck. In vivo experiments. When the parakeets were injected with 3H-5-HTP alone or pretreated with drugs interfering with monoamine metabolism (e.g. R04-4602, nialamide) prior to injection of the label, the SRP cells always exhibited specific radioautographic rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

1977
1977
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…As a result of this study and other cytophysiologicat inVestigat!ons on the pineal of Lacertilians and biochemical tindings in birds, it is proposed that pathways of synthesis and metabolism of 5-HT are located in SRP cells. The distribution of endogenous arid exogenous (Collin et al, 1976) indoleamines is similar. …”
mentioning
confidence: 83%
See 1 more Smart Citation
“…As a result of this study and other cytophysiologicat inVestigat!ons on the pineal of Lacertilians and biochemical tindings in birds, it is proposed that pathways of synthesis and metabolism of 5-HT are located in SRP cells. The distribution of endogenous arid exogenous (Collin et al, 1976) indoleamines is similar. …”
mentioning
confidence: 83%
“…The amines and perhaps also protein(s), are involved in some endocrine mechanisms (for references see Collin et al, 1976). These properties allow to consider the avian pineal organ to be a photo-neuroendocrine organ (Coltin, 1971;Oksche and Hartwig, 1975).…”
Section: Introductionmentioning
confidence: 98%
“…In some species, serotonin was localized in pinealocytes autoradiographically and by the Falk Hillarp method (Wartenberg and Baumgarten, 1969;Ueck, 1973;Collin et al, 1976). Using the immunoglobulin-gold method (Vigh, 1987;Vigh and VighTeichmann, 1988) serotonin immunoreaction was found in the neurohormonal terminals of the pinealocytes of the pigeon (Fig.…”
Section: Immunocytochemistry Of Transmitter Substancesmentioning
confidence: 98%
“…N-acetyl-5-methoxytryptamine (aMT), 5-methoxytryptophol (ML), 5-methoxytryptamine (MT), considered as pineal neurohormones) [9,18,32], From the auto radiographic experiments [6,9,10,18,31], it is concluded that indoles arc produced and stored mainly in the perikaryon and basal pedicle of MP. MP also seem to release indoles directly into the systemic ciculation.…”
Section: Coexistence Of Several Secretory Products (Indoles and Peptimentioning
confidence: 99%
“…The principal steps of indole metabolism in birds have been reviewed [ 10,18,33]. The synthesis of indoles undergoes striking circadian and circannual changes [1,30,33].…”
Section: Coexistence Of Several Secretory Products (Indoles and Peptimentioning
confidence: 99%